PENGARUH FAKTOR EKONOMI TERHADAP INDEKS SAHAM SYARIAH DI JAKARTA ISLAMIC INDEX (JII) 2015-2024 (Universitas Islam Negeri Alauddin Makassar, 2026)
This study aims to analyze the effect of inflation and the rupiah exchange rate on the Jakarta Islamic Index (JII) during the period 2015-2024. The study uses a quantitative approach with monthly secondary data from Investing, the Ministry of Trade, the Indonesia Stock Exchange, and Bank Indonesia. The analysis was conducted using OLS multiple linear regression through EViews 13 and tested with classical assumptions to ensure the validity of the model. The results show that inflation has a negative but insignificant effect on the Sharia stock index (JII), as changes in inflation are not strong enough to influence the movement of the index, which is more determined by fundamental performance and the real sector. The rupiah exchange rate also has no significant effect on the JII, as its fluctuations do not directly influence the decisions of long-term Sharia investors. Simultaneously, both variables have no significant effect, indicating that the performance of sharia stocks is more influenced by fundamental factors than macroeconomic conditions. The contribution of this study lies in its long observation period, which covers the economic recovery phase. The limitation of this study is the limited scope of variables. The implication is that the Sharia Stock Index (JII) can be considered a relatively stable investment instrument.